A case of antiphospholipid syndrome presenting cryptogenically as Budd-Chiari syndrome, then fulminantly as Libman-Sacks endocarditis. Issue 5 (14th May 2019) - Goldhar, Hart A; O'Meara, Paloma; Castellucci, Lana A
Abstract : A 58 year-old left-handed woman was transferred to our hospital with an evolving left middle cerebral artery stroke, severe thrombocytopenia and elevated inflammatory markers. She had a history of chronic Budd-Chiari syndrome (BCS) 16 months prior, attributed to a calcified web in the inferior vena cava that was stented. No thrombophilia testing was performed at that time. The current presentation demonstrated dense right-sided facial and arm paresis and neglect. Erythrocyte sedimentation rate and C-reactive protein were elevated, an autoimmune workup was consistent with a new diagnosis of systemic lupus erythematosus and triple-positive antiphospholipid antibodies. A transesophageal echocardiogram demonstrated a vegetation consistent with Libman-Sacks endocarditis (LSE), thought to have embolised to the brain. The patient was treated acutely with steroids, intravenous immunoglobulin and clopidogrel. This case demonstrates an atypical constellation of the antiphospholipid syndrome, with a novel presentation of BCS and LSE, and reinforces the importance of hypercoagulability screening in this population.